Nasal Tip Shaping Finesse in Rhinoplasty. Issue 6 (29th November 2021) - Savetsky, Ira L.; Avashia, Yash J.; Rohrich, Rod J.
Abstract : Summary: Anatomic subtleties of the nasal tip have a dramatic impact on the overall appearance of the nose. Mastery of normal nasal aesthetics and anatomy is a critical prerequisite to adeptly performing nasal tip refinement during open rhinoplasty. This article and series of videos aim to provide a focused review of nasal tip analysis, anatomy, and surgical technique, with particular emphasis on pertinent tip sutures and cartilage grafts.